THE IMPLEMENTATION OF ENGLISH BRIDGING PROGRAM ADAPTING CAMBRIDGE CURRICULUM FOR PRIMARY SCHOOL - Mahmudah, Mahmudah; Kholis, Adhan (Prominent, 2023)
This study aims to explore and describe English bridging program adapting Cambridge curriculum for grade one of primary school at Afkaaruna Islamic School (AIS), Yogyakarta. The bridging program was a program to facilitate new students to improve their English language skills before joining real class. This study used qualitative approach with the case study research design. To collect the data, the researcher used interview, observation, and documentation. The researchers interviewed three English teachers. Then, data were analysed using the theory of Miles and Huberman including data collection, data reduction, data display and conclution/verifying. The results included the implementation of the Bridging Program was carried out for 2 to 3 months with the three focused subjects: Indonesian literacy, English literacy, attitude and character. Activities done included a pre-test conducted to determine students' abilities. The obstacles during the learning process were during online learning and the gap in students' abilities. The solution given was to provide additional classes for students who had not reached the learning target. The benefit of implementing English Bridging Program was to help students prepare themselves in the learning process and improve students' English ability to communicate and interact with others.